Life as we made it : how 50,000 years of human innovation refined--and redefined--nature - Shapiro, Beth Alison (Basic Books, 2021)
"Humans seem to be destroying nature with incessant fiddling. We can use viruses to insert genes for pesticide resistance into plants, or to make the flesh of goldfish glow. We can turn bacteria into factories for millions of molecules, from vitamin A and insulin to diesel fuel. And this year's Nobel Prize went to the inventors of tool called CRISPR, which lets us edit genomes almost as easily as we can edit the text in a computer document. The potential for harm can seem both enormous and inevitable. In Life as We Made It, evolutionary biologist Beth Shapiro argues that our fears of new technologies aren't just mistaken, but they miss the big picture about human history: we've been remaking nature for as long as we've been around. As Shapiro shows, the molecular tools of biotechnology are just the latest in a long line of innovations stretching back to the extra food and warm fires that first brought wolves into the human fold, turning them into devoted dogs. Perhaps more importantly, Shapiro offers a new understanding of the evolution of our species and those that surround us. We might think of evolution as a process bigger than humans (and everything else). To the contrary, Shapiro argues that we have always been active participants in it, driving it both inadvertently and intentionally with our remarkable capacity for technological innovation. Shapiro shows that with each innovation and every plant and animal we touched, we not only shaped our own diets, genes, and social structures but we reset the course of evolution, both theirs and ours. Indeed, although we think of only modern technology as capable of gene editing, she shows that even the first stone tools could edit DNA, simply by changing the world in which all life lives. Recasting the history of biology and technology alike, Life as We Made It shows that the history of our species is essentially and inevitably a story of us meddling with nature. And that ultimately, our species' fate depends on how we do it in the future"--